HUBUNGAN MOTIVASI DENGAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMPN 43 MERANGIN - Doki Tamario; Ferinaldi; Hasmawati (Mat-Edukasia, 2021)
This research is a correlation study with a quantitative approach. The data collection techniques used in this study were questionnaire techniques and documentation methods. The population and sample in this study were students of Class VIII SMP Negeri 43 Merangin. The data analysis technique used is the Normality Test, Linearity, and Hypothesis Test. Based on the results of the analysis with the product moment correlation, it shows that there is a relationship between learning motivation and learning outcomes in Mathematics for class VIII grade SMP Negeri 43 Merangin. This is indicated by the magnitude of the r count value is greater than the r table (0.6430> 0.413) and a significance value of 0.000 which means less than 0.05 (0.000 <0.05), so this study succeeded in proving the hypothesis which states that "There is a positive relationship. and significant learning motivation with the learning outcomes of class VIII class of SMP Negeri 43 Merangin Mathematics, and the value of the coefficient of determination is calculated by the formula kd r2 x 100% so that learning motivation affects the learning outcomes of grade VIII students of SMP Negeri 43 Merangin by about 41.35%. And the rest is influenced by other factors.